In vitro study of proliferation and differentiation cells potention, derived from embryonal human brain - Semenova, V. M.; Lyubych, L. D.; Lisyany, N. I.; Petrenko, A. Yu.; Stayno, L. P. (Ukrainian Neurosurgical Journal, 2007)
The proliferation potention and influence of some biomedicines on neuronal differentiation cytostructural peculiarities of the cultivated neural precursors, derived from human cryopreserved neurocells were studied. Proliferying neurocells population was vimentin-positive. The cultivation in vitro of neuronal precursors in DMEM without serum with insulin-transferrin-selenit addition did not lead to their terminal differentiation. Сultivation with retinoic acid stimulated the neuronal-way differentiating cells growth. Some neural precursors differentiated in glyocytes and were GFAP-positive. The obtained results evidence about saved capacity of both neuronal and glyal differentiation ways of cell precursors, derived after long-term cultivation in suspension in DMEM.